Anatomical Variation of the Tarsus in Common Inbred Mouse Strains. Issue 3 (31st October 2016) - Richbourg, Heather A.; Martin, Matthew J.; Schachner, Emma R.; McNulty, Margaret A.
ABSTRACT: Rodent models are used for a variety of orthopedic research applications; however, anatomy references include mostly artistic representations. Advanced imaging techniques, including micro‐computed tomography (microCT), can provide more accurate representations of subtle anatomical characteristics. A recent microCT atlas of laboratory mouse ( Mus musculus) anatomy depicts the central and tarsal bone III (T3) as a single bone, differing from previous references. Fusion of tarsal bones is generally characterized as pathological secondary to mutations associated with growth factors, and normal variation has not been documented in the mouse tarsus. Therefore, it is unclear if this fusion is a normal or a pathological characteristic. The aim of this study is to characterize the tarsus of the laboratory mouse and compare it to the rat and selected outgroup species (i.e., white‐footed mouse) via microCT and histology to determine if the central and T3 are separate or fused into a single bone. Laboratory mice (C57/Bl6 [ n = 17] and BalbC [ n = 2]) and rats ( n = 5) were scanned with microCT. A representative laboratory mouse from each strain was evaluated histologically via serial sagittal sections through the mid‐tarsus. General pedal anatomy was similar between all species; however, the central and T3 bones were fused in all laboratory mice but not the rat or white‐footed mouse. A band of hyaline cartilage was identified within the fused bone of the laboratory mice. We conclude that the fusion found is a normal characteristic in laboratory mice, but timing of the fusion remains ambiguous. Anat Rec, 300:450–459, 2017. © 2016 Wiley Periodicals, Inc.